Auf dem Weg der Integration: Vorstellung einer gegenwärtig laufenden empirischen Untersuchung von Langzeitarbeitslosen - Pilinszky, Attila; Ládonyi, Zsuzsanna (European Journal of Mental Health, 2008)
On the Road to Integration: Introducing an Empirical Study in Progress Examining Longterm Unemployed People: The aim of the paper is to study the integration of the long-term unemployed into society. In recent years assistance provided to long-term unemployed in Hungary has changed several times. One of the major changes is that social work plays a more significant role in helping the client group; however, the profession also needs to be prepared for this. Social institutions face new challenges in dealing with the large number of the long-term unemployed people. The report briefly describes research hypotheses and the study sample. Over the course of the study people in a Budapest district receiving regular social assistance are examined in the dimensions of their relation to the world of employment and ‘disaffiliation’.